Exploring the pedagogical possibilities of Indigenous sport-for-development programmes using a socio-personal approach. Issue 4 (18th May 2016) - Rynne, Steven
Abstract : This paper considers the pedagogical properties and subsequent impact of sport-for-development programs across a variety of sites in Australia. Moreover, this research adopts a socio-personal account of learning in an attempt to examine the contributions of the social and physical worlds related to surfing programs as well as the individuals' role in construing and constructing meaning through participation in these worlds. The major learning stories that emerged from this research were in relation to connections with and learning from the ocean, programme providers, Indigenous peers and Indigenous community members. More specifically, learning reportedly related to spiritual (re)connection with land and ocean, the (re)development of Indigenous and surf-specific cultural knowledge, and the (re)establishment of familial and community bonds. While these stories are significant in their own right, the learning affordances present in these programs are worthy of further attention. Indeed, the contributions of the physical and social environments at each site had important implications for the overall pedagogical properties of the programs. For example, the physical conditions of the surf as well as the features of the coastal landscapes served to shape the activities and interactions of individuals within the programs. In a similar fashion, the contributions of program leaders impacted directly on the nature and direction of learning through the organisation and support of the social environment as did the personal agency of the individual learners. Through a socio-personal approach it is possible to consider the contributions of the social and physical world, how individuals engage, construe, construct and reconcile their experiences and the relations between all of these components when learning in sport-for-development settings.